Quantum-trajectory analysis for charge transfer in solid materials induced by strong laser fields. (6th June 2017) - Jiang, Shicheng; Yu, Chao; Yuan, Guanglu; Wu, Tong; Wang, Ziwen; Lu, Ruifeng
Abstract: We investigate the dependence of charge transfer on the intensity of driving laser field when SiO2 crystal is irradiated by an 800 nm laser. It is surprising that the direction of charge transfer undergoes a sudden reversal when the driving laser intensity exceeds critical values with different carrier–envelope phases. By applying quantum-trajectory analysis, we find that the Bloch oscillation plays an important role in charge transfer in solids. Also, we study the interaction of a strong laser with gallium nitride (GaN), which is widely used in optoelectronics. A pump–probe scheme is applied to control the quantum trajectories of the electrons in the conduction band. The signal of charge transfer is controlled successfully by means of a theoretically proposed approach.